Investigating the role of PPARβ/δ in retinal vascular remodeling using Pparβ/δ-deficient mice - Ho, Sze Yuan (2020)
Peroxisome proliferator-activated receptor (PPAR)β/δ is a member of the nuclear receptor superfamily of transcription factors, which plays fundamental roles in cell proliferation and differentiation, inflammation, adipogenesis, and energy homeostasis. Previous studies demonstrated a reduced choroidal neovascularization (CNV) in Pparβ/δ-deficient mice. However, PPARβ/δ's role in physiological blood vessel formation and vessel remodeling in the retina has yet to be established. Our study showed that PPARβ/δ is specifically required for disordered blood vessel formation in the retina. We further demonstrated an increased arteriovenous crossover and wider venous caliber in Pparβ/δ-haplodeficient mice. In summary, these results indicated a critical role of PPARβ/δ in pathological angiogenesis and blood vessel remodeling in the retina.